2005
DOI: 10.1007/s00442-005-0215-0
|View full text |Cite
|
Sign up to set email alerts
|

Host physiological condition regulates parasitic plant performance: Arceuthobium vaginatum subsp. cryptopodum on Pinus ponderosa

Abstract: Much research has focused on effects of plant parasites on host-plant physiology and growth, but little is known about effects of host physiological condition on parasite growth. Using the parasitic dwarf mistletoe Arceuthobium vaginatum subsp. cryptopodum (Viscaceae) and its host Pinus ponderosa, we investigated whether changes in host physiological condition influenced mistletoe shoot development in northern Arizona forests. We conducted two studies in two consecutive years and used forest thinning (i.e., co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 59 publications
0
26
0
3
Order By: Relevance
“…Its photoassimilates are therefore significantly enriched in 13 C compared to those of C 3 plants due to the differential isotope discrimination of RUBISCO and PEPC, primary CO 2 -fixing enzymes in C 3 and environmental stress such as water deficiency. 46 Dwarf-mistletoes (genus Arceuthobium) that are considered to be dependent on host-derived organic carbon (based on gasometric measurements; 47,48 no detailed carbon budget studies are available) tend to perform better on vigorous host that are in a good physiological state. 48,49 Nonetheless, even these highly heterotrophic species were demonstrated to produce more aerial shoots under high irradiance which is however not likely to be underpinned by a causal dependence of parasite performance on the light level.…”
Section: Heterotrophic Carbon Gainmentioning
confidence: 99%
See 1 more Smart Citation
“…Its photoassimilates are therefore significantly enriched in 13 C compared to those of C 3 plants due to the differential isotope discrimination of RUBISCO and PEPC, primary CO 2 -fixing enzymes in C 3 and environmental stress such as water deficiency. 46 Dwarf-mistletoes (genus Arceuthobium) that are considered to be dependent on host-derived organic carbon (based on gasometric measurements; 47,48 no detailed carbon budget studies are available) tend to perform better on vigorous host that are in a good physiological state. 48,49 Nonetheless, even these highly heterotrophic species were demonstrated to produce more aerial shoots under high irradiance which is however not likely to be underpinned by a causal dependence of parasite performance on the light level.…”
Section: Heterotrophic Carbon Gainmentioning
confidence: 99%
“…46 Dwarf-mistletoes (genus Arceuthobium) that are considered to be dependent on host-derived organic carbon (based on gasometric measurements; 47,48 no detailed carbon budget studies are available) tend to perform better on vigorous host that are in a good physiological state. 48,49 Nonetheless, even these highly heterotrophic species were demonstrated to produce more aerial shoots under high irradiance which is however not likely to be underpinned by a causal dependence of parasite performance on the light level. It is more probable that the dwarf-mistletoe is indirectly positively affected by increased photosynthetic capacity of highly irradiated branch or by elevated temperature.…”
Section: Heterotrophic Carbon Gainmentioning
confidence: 99%
“…Recent evidence indicates that the success of dwarf mistletoe depends largely upon the physiological condition of the host trees (Bickford et al 2005), suggesting that the faster growing trees may be more suitable hosts for the mistletoe. Other studies, however, have found a greater abundance of mistletoe on trees growing in stressful conditions (Gehring and Whitham 1995).…”
Section: Mean Growth Ratesmentioning
confidence: 99%
“…Para el bosque semidenso el porcentaje de árboles infestados incrementó 16.1% (Tabla 2), debido a que la baja densidad arbórea estimula el desarrollo de los brotes aéreos y por ende la propagación del muérdago enano (Bickford et al, 2005). En contraste, el bosque denso registró una disminución en el porcentaje de árboles infestados (Tabla 3), debido a la inclusión de individuos en la categoría < 5 (32.2%) que no fueron considerados en la primera evaluación, ya que no cumplían con la talla (DN) y altura considerada para el presente estudio, sin embargo, en las subsecuentes evaluaciones se incorporaron.…”
Section: Grado De Infección En áRboles No Tratadosunclassified